Does the Gospel of Matthew Proclaim Mary's Virginity? - Isbell, Charles D. (1977)
In a recent BAR article, Père Benoit’s explanation of Isaiah 7:14 and Matthew 1:23 was quoted without comment and apparently accepted at face value.a Dr. Dwight Young and I have recently completed an extensive study of the concept of virginity in the world of the Bible.b Since some of our conclusions bear upon this […]